2019
DOI: 10.1097/prs.0000000000006227
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results Supporting the Bacterial Hypothesis in Red Breast Syndrome following Postmastectomy Acellular Dermal Matrix– and Implant-Based Reconstructions

Abstract: Summary: Acellular dermal matrices have become a mandatory tool in reconstructive breast surgery. Since their introduction, they have been considered to be nonreactive and nonimmunogenic scaffolds. However, some patients who undergo implant-based breast reconstruction with acellular dermal matrices develop postoperative cutaneous erythema overlying their matrices, a condition commonly referred to as red breast syndrome. The aim of this study was to gain a better understanding of this phenomenon. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These findings support the direction of other studies which have reported significant differences in the total number of days to drain removal in favor of DermACELL. 24,[33][34][35][36] This trend may be explained by subtle differences in the fenestrations of the natural material, which could allow fluid from the ADM to escape and facilitate more efficient drainage. 37 This could also be due to DermACELL's advantage in promoting host tissue integration and revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the direction of other studies which have reported significant differences in the total number of days to drain removal in favor of DermACELL. 24,[33][34][35][36] This trend may be explained by subtle differences in the fenestrations of the natural material, which could allow fluid from the ADM to escape and facilitate more efficient drainage. 37 This could also be due to DermACELL's advantage in promoting host tissue integration and revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…29 Bacterial contamination has also been implicated in an inflammatory condition, the red breast syndrome, in 4 to 14 percent of patients undergoing acellular dermal matrix implant reconstruction, as evidenced by the presence of bacteria in cultures and electron microscopy from biofilm specimens surrounding the implant. 30 In addition, bacteria have been present in the biofilm of asymptomatic patients with acellular dermal matrix reconstruction. 31 Other experimental bioassay studies have shown a significant increase in Staphylococcus aureus adherence to acellular dermal matrix compared to nonbiological synthetic compounds such as prolene.…”
Section: Safety Of Acellular Dermal Matrix In Prepectoral Reconstructionmentioning
confidence: 99%
“…Six series describing early outcomes after prepectoral breast reconstruction also include outcomes to describe patient function and/or postoperative pain during recovery with favorable results when compared to partially submuscular patient cohorts. 20,21,35,[43][44][45][46][47][48][49][50][51] The studies were similarly powered, with 24 to 39 patients per study undergoing prepectoral breast reconstruction. Five of the six patient series reported significantly lower patient-reported pain scores in the prepectoral groups than partially submuscular comparison cohorts.…”
Section: Functional Outcomes Postoperative Pain and Recoverymentioning
confidence: 99%
“…Currently, there are no studies describing red breast syndrome in prepectoral breast reconstruction, potentially because of its now lower incidence in acellular dermal matrix-assisted breast reconstruction as a whole (1.7 to 14 percent) with improved technique and technology. 44…”
Section: Ementioning
confidence: 99%